More active pre-school children have better motor competence at school starting age: an observational cohort study - Lisa M. Barnett; Jo Salmon; Kylie D. Hesketh (BMC, 2016)
Abstract Background Almost half of young children do not achieve minimum recommendations of 60 daily minutes in physical activity. Physical activity is potentially an important determinant of the development of motor competence in children. This study is one of very few longitudinal studies in this area and the first to investigate early childhood physical activity as a predictor of subsequent motor skill competence. Methods Children were assessed as part of the Melbourne InFANT Program longitudinal cohort study at 19 months, 3.5 years and 5 years. Moderate-to-vigorous physical activity (MVPA) (accelerometry) was assessed at each time point. At age 5, children were also assessed in actual (Test of Gross Motor Development-2) and perceived motor competence (Pictorial Scale of Perceived Movement Skill Competence). General linear models were performed with all 12 skills (six object control and six locomotor skills), both actual and perceived, at age 5 as the respective outcome variables. Predictor variables alternated between MVPA at 19 months, 3.5 years and 5 years. Results Based on standardized TGMD-2 scores most children were average or below in their skill level at age 5. MVPA at 19 months was not a predictor of actual or perceived skill at age 5. MVPA at 3.5 years was associated with actual locomotor skill (B = 0.073, p = 0.033) and perceived total skill at 5 years of age (B = 0.059, p = 0.044). MVPA was not a predictor of actual or perceived object control skill at any age. Conclusion Parents and preschool staff should be informed that more time in MVPA as a preschool child contributes to locomotor skill and to perceptions of skill ability in a child of school starting age. Understanding this relationship will assist in intervention development.